Magnetic properties of NiCuZn ferrites synthesized by oxalate precursor method - Ghodake, S. A.; Ghodake, U. R.; Sawant, S. R.; Suryavanshi, S. S.; Bakare, P. P. (Journal of Magnetism and Magnetic Materials, 2006)
Ni-Cu-Zn ferrites have been synthesized by employing co-precipitation technique using oxalate precursors. X-ray diffractograms did not show impurity phases, indicating single-phase formation of the ferrites. The diffractograms of oxalate complex decomposed at 650 degrees C show that ferritization is complete up to 650 degrees C. Lattice parameter a (angstrom) was found to decrease with the addition of Ni2+ which is attributed to ionic sizes of Ni2+ (0.69 angstrom), which replaces Cu2+ (0.72 angstrom). From the thermogravimetric studies it is observed that the experimentally observed total mass loss (%), agrees with theoretically calculated mass loss (%) indicating maintenance of requisite stoichiometry. Initial permeability (mu(i)) shows increase when Ni2+ is added up to x = 0.15 while for (x > 0. 15), it decreases. The increase in initial permeability (mu(i)) is attributed to monotonic increase in Ms, and K-1 on addition of Ni2+. However, the microstructure and density (porosity) also influence mu(i) variations. The decrease in pi is attributable to increase of K-1. The composition with density 91.14% exhibits large mu(i) which also tends to increase with temperature up to 60 degrees C. Thus its usable range extends up to 60 degrees C. This samples has T-c near to 160 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: initial permeability; magneticproperties; Magnetization; NiCuZn ferrites; XRD